Nexus of tourism affinity, perceived behavioral control and green environmental literacy in support of regenerative tourism - Umer Zaman (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
The inevitable transition to the green economy has ignited the "green, blend and extend" solutions for the global tourism industry. Regenerative tourism has recently gained global attention as it offers a virtuous cycle of positive impacts on the ecological environment, economies and local communities at host destinations. Despite the alarming situation of environmental degradation and the worsening condition of destinations in crisis, empirical research on regenerative tourism has rarely been attempted. The present research examined the impact of tourism affinity on the support for regenerative tourism, and whether perceived behavioral control and green environmental literacy moderate this relationship. Using structural equation modeling (SEM) on the study data from international expats (N=290) residing in the United Arab Emirates (UAE), the empirical evidence validated the conceptual model. PLS-SEM estimations indicated that the support for regenerative tourism is significantly and positively influenced by tourism affinity. Importantly, perceived behavioral control and green environmental literacy significantly strengthened the relationship between tourism affinity and support for regenerative tourism. The present study's focus on expatriates and their engagement in regenerative tourism in the UAE is novel, as influenced by tourism affinity within a moderating mechanism of perceived behavioral control and green environmental literacy.
Keywords: 330; Tourism affinity; regenerative tourism; perceived behavioral control; green environmental literacy; COP26; theory of planned behavior; United Arab Emirates